(untitled) (Damascus University Journal of arts and humanities sciences, 2021)
Egyptian civilization produced a literature that was known as the advice literature and just eight papyruses came from this literature. These papers were named according to the names of their wisers who wrote them and they were put in the historical order as proverbs and wisdoms, Patah-hotep" and"Kajmni" instructions, and both are from the old country, "Mrecara" instructions from the feudal region, and "Amnmhat" commandments to his son "Snosert", and "step up-waa" instructions, and other instructions from the medieval country and "Anny" instructions, and "Amnmoby" instructions from the modern country. These wisdoms and instructions weren’t specified to any times, but they expanded to cover all the Egyptian Times and included every part in the life issues such as; marriage, learning, board decency and others. These wisdoms and instructions produced the extract of life experience and signified the happiness way to Egyptians and put the highest values that could be a guide to the life in their hands, and organized the social relations among peoples. They aimed to give advice to make successful persons in their life, family, and children as well as to make good relations with their mothers or fathers, and to be a successful clerk in his work that should be done properly. They also guide man to study life and deal with every part of it and how to talk and answer well. That leads to success and development in the life. In addition, these pieces of advice are enough to eternalize the memorial of authors and wisers who are the most important than pyramids and graves building. By guiding and advising in the old Egypt, we guarantee of having educated fathers and civilian or clergymen teachers, authors who ascribed their advice to their personal and ancestors experiences that weren’t ascribed to the heaven inspiration or to the Gods’ orders